Integrative analysis revealed that distinct cuprotosis patterns reshaped tumor microenvironment and responses to immunotherapy of colorectal cancer - Xu, Ximo; Ding, Chengsheng; Zhong, Hao; Qin, Wei; Shu, Duohuo; Yu, Mengqin; Abuduaini, Naijipu; Zhang, Sen; Yang, Xiao; Feng, Bo (Frontiers in Immunology, 2023)
Background: Cuprotosis is a novel form of programmed cell death that involves direct targeting of key enzymes in the tricarboxylic acid (TCA) cycle by excess copper, and may result in mitochondrial metabolic dysfunction. However, whether cuprotosis may mediate the tumor microenvironment (TME) and immune regulation in colorectal cancer (CRC) remains unclear. Methods: 10 cuprotosis-related genes were selected and unsupervised consensus clustering was performed to identify the cuprotosis patterns and the correlated TME characteristics. Using principal component analysis, a COPsig score was established to quantify cuprotosis patterns in individual patients. Top 10 important cuprotosis signature genes were analyzed in single cell transcriptome data. Results: Three distinct cuprotosis patterns were identified. The TME cell infiltration characteristics of three patterns were associated with immune-excluded, immune-desert, and immune-inflamed phenotype, respectively. Based on individual cuprotosis patterns, patients were assigned into COPsig high and low score groups. Patients with higher COPsig score were characterized by longer overall survival time, lower immune cell as well as stromal infiltration, greater tumor mutational burden. Moreover, further analysis demonstrated that CRC patients with higher COPsig score were more likely to response to immune checkpoint inhibitors and 5-FU chemotherapy. Single cell transcriptome analysis indicated that cuprotosis signature genes recruited tumor-associated macrophages to TME through the regulation of TCA and the metabolism of glutamine and fatty acid, thus influencing the prognosis of CRC patients. Conclusion: This study indicated that distinct cuprotosis patterns laid a solid foundation to the explanation of heterogeneity and complexity of individual TME, thus guiding more effective immunotherapy as well as adjuvant chemotherapy strategies.